2008
DOI: 10.1128/ec.00149-08
|View full text |Cite
|
Sign up to set email alerts
|

The Crucial Role of the Pls1 Tetraspanin during Ascospore Germination in Podospora anserina Provides an Example of the Convergent Evolution of Morphogenetic Processes in Fungal Plant Pathogens and Saprobes

Abstract: Pls1 tetraspanins were shown for some pathogenic fungi to be essential for appressorium-mediated penetration into their host plants. We show here that Podospora anserina, a saprobic fungus lacking appressorium, contains PaPls1, a gene orthologous to known PLS1 genes. Inactivation of PaPls1 demonstrates that this gene is specifically required for the germination of ascospores in P. anserina. These ascospores are heavily melanized cells that germinate under inducing conditions through a specific pore. On the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 53 publications
(82 reference statements)
3
82
0
Order By: Relevance
“…To check that we correctly identified the borders of the recombination-less region, we genetically mapped several markers with respect to the mating type (Figure 1). The markers were obtained by gene replacements or classical genetics in diverse projects prior to this study (Silar and Picard 1994;Silar et al 1997;Graïa et al 2000;Contamine et al 2004;Bonnet et al 2006;Lambou et al 2008;J. Ait-Benkhali, E. Coppin, and R. Debuchy, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…To check that we correctly identified the borders of the recombination-less region, we genetically mapped several markers with respect to the mating type (Figure 1). The markers were obtained by gene replacements or classical genetics in diverse projects prior to this study (Silar and Picard 1994;Silar et al 1997;Graïa et al 2000;Contamine et al 2004;Bonnet et al 2006;Lambou et al 2008;J. Ait-Benkhali, E. Coppin, and R. Debuchy, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…We found that NOX2 is required for germination of melanized ascospores only, since melanin-deficient ascospores from Δnox2 are able to germinate. Lambou et al (2008) suggested for P. anserina that the weakened cell wall of pigment-deficient ascospores and the absence of melanin either triggered the germination process or prevented its inhibition. However, the ROS scavenging capacity of melanin (Riley 1997) might also play a role in this process.…”
Section: Transcriptional Profiling Reveals Differentially Regulated Gmentioning
confidence: 99%
“…Another candidate NOX regulatory protein is tetraspanin Pls1. Strains from different ascomycetes, lacking the corresponding gene, have phenotypes similar to nox2 deletion strains (Lambou et al 2008;Ryder et al 2013;Siegmund et al 2013). However, very little is known about the upstream and downstream components of the NOX signaling pathways in fungi.…”
mentioning
confidence: 99%
“…The DPaMpk1, IDC 404 PaMKK1, and IDC 118 PaASK1 mutants have been previously described and differ from wild type by a single mutation (Kicka and Silar 2004;Kicka et al 2006) as do the pks1-193 mutants (Coppin and Silar 2007). Construction of the Dmus51::su8-1 strain lacking the mus-51 subunit of the complex involved in end joining of broken DNA fragments was described previously (Lambou et al 2008). DNA integration in this strain proceeds almost exclusively by homologous recombination.…”
Section: Strains and Growth Conditionsmentioning
confidence: 99%
“…A XhoI site in M3K2DF and an EcoRV one in M3K2DR allowed the release from the pGEMT vector of the corresponding 39 noncoding fragment, which was then cloned at the XhoI/ EcoRV sites into the plasmid harboring the PaMkk3 59 noncoding fragment, generating the pDPaMkk3 plasmid. Transformation of the P. anserina Dmus51::su8-1, pks1-193 strain (Lambou et al 2008) was performed using pDPaMkk3 plasmid previously linearized at the unique EcoRV site to generate homologous recombination ends. Three hygromycine B-resistant transformants were selected for further analyses.…”
Section: Deletions Of the Mapk Mapkk And Mapkkk Genesmentioning
confidence: 99%